Penerapan Metode Building Information Modeling (BIM) 5D dalam Pembangunan Rumah Tinggal - Agustin, Bintang Fajar; Hendriyani, Irna; Devi, Suheria Mulia (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Technological advances in the construction world are beneficial, among others, to support modeling, planning, cost estimation, mass changes, building continuity, and building management. A technology that is widely used in the construction industry is Building Information Modeling (BIM). Accuracy in estimating construction costs is necessary to achieve an effective value during the planning process. Budgeting for development projects still uses traditional methods for much better results. Therefore, this study uses the concept of 5D dimensional BIM to analyze the volume and cost using the concept (BIM) with conventional methods on the work of the 2-story structure of a type 170 house in Balikpapan City. The results of the research on the construction structure of a 2-story home in the city of Balikpapan using the 5D BIM concept with a concrete volume of 2661.69 kg for Rp 46,812,00389.24 and a concrete volume of 27.13 m3 for Rp 56,203,185.16. The difference in iron volume is 19.52%. Meanwhile, the difference in concrete volume is 15.60%, which means that the calculation using the 5D Building Information Modeling (BIM) concept supported by Autodesk Revit software is lower than planned.